2017
DOI: 10.1515/reveh-2016-0050
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of xenobiotic detoxification enzymes in metabolic diseases

Abstract: Abstract Mammalian systems have developed extensive molecular mechanisms to protect against the toxicity of many exogenous xenobiotic compounds. Interestingly, many detoxification enzymes, including cytochrome P450s and flavin-containing monooxygenases, and their associated transcriptional activators [e.g. the aryl hydrocarbon receptor (AhR)], have now been shown to have endogenous roles in normal physiology and the pathology of metabolic diseases. This mini-review will focus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Generally, xenobiotic metabolism contributes to the detoxification of poisonous compounds [ 32 ]. This process consists of phase I, II, and III, and the enzymes involved in this process are known as xenobiotic-metabolizing enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, xenobiotic metabolism contributes to the detoxification of poisonous compounds [ 32 ]. This process consists of phase I, II, and III, and the enzymes involved in this process are known as xenobiotic-metabolizing enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis, exposure to some environmental pollutants has been associated with metabolic syndrome. Although the mechanisms are still largely unexplored, the activities of certain XME seem likely to interfere with energy balance . Our present work follows three recent articles that have revealed a possible link between the activities of arylamine N ‐acetyltransferases (NAT) and energy metabolism.…”
mentioning
confidence: 85%
“…Two other reports examining mFmo1 and mFmo5 knock-out mice, respectively, found that both were capable of altering metabolism and energy balance sufficiently to cause gross alterations in body size (58,59). A recent review discusses these mFMO-related effects on carbohydrate and lipid metabolism and energy balance (60).…”
Section: Diabetes and Metabolic Disordersmentioning
confidence: 99%